2017
DOI: 10.1117/12.2286161
|View full text |Cite
|
Sign up to set email alerts
|

Focus classification in digital holographic microscopy using deep convolutional neural networks

Abstract: In digital holographic microscopy, one often obtains an in-focus image of the sample by applying a focus metric to a stack of numerical reconstructions. We present an alternative approach using a deep convolutional neural network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…The greatest benefit of the deep learning method outlined in this paper is that after training, the in-focus depth can be obtained from the hologram plane intensity directly, in constant time, without any numerical propagation. It should be noted that this paper extends results reported in [26,27] by rigorously verifying the performance of the approach in a regression context. Ren et al [30] reported a deep-learning-based approach for both amplitude and phase objects.…”
Section: Digital Holographic Microscopysupporting
confidence: 75%
See 2 more Smart Citations
“…The greatest benefit of the deep learning method outlined in this paper is that after training, the in-focus depth can be obtained from the hologram plane intensity directly, in constant time, without any numerical propagation. It should be noted that this paper extends results reported in [26,27] by rigorously verifying the performance of the approach in a regression context. Ren et al [30] reported a deep-learning-based approach for both amplitude and phase objects.…”
Section: Digital Holographic Microscopysupporting
confidence: 75%
“…In a rigorous treatment of our preliminary results [26,27], one of the first applications of deep learning to digital holographic microscopy, we show that a deep artificial neural network can be designed to learn the appropriate in-focus depth of an arbitrary MDCK cell cluster encoded in a digital hologram. Its greatest benefit is that the in-focus depth can be obtained from the hologram plane intensity only, and in constant time, without any numerical propagation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Fig. 8(g), the Region-recognition Filter (F RR ) is built with shape recognition of the spectrum and iterative calculation of threshold [21] and the shape of filtered spectrum is consistent with the energy distribution of + 1 term. In Fig.…”
Section: Experimental Testing and Resultsmentioning
confidence: 99%
“…Recently, deep learning has been introduced to reconstruction processes of digital holography, such as autofocusing [21], phase aberration compensations [22], etc. The technique can realize adaptation and full automation because it takes pre-labeled results as a guide to learn the intrinsic features of the data set.…”
Section: Introductionmentioning
confidence: 99%